Polysaccharide-Stabilized Butterfly Pea Flower (Clitoria ternatea) Anthocyanin as Natural Photosensitizer against MRSA: In Silico and In Vitro Evaluation - Siti Humairoh; M. Akram; Rumiyati Dwi Nindi Marrisca; Aisyah Pratiwi; Ade Fadilah; Mardiyanto; Miksusanti; Najma Annuria Fithri (Science and Technology Indonesia, 2026)
Butterfly pea flower (Clitoria ternatea) anthocyanins have potential as natural photosensitizers for photothermal–photodynamic therapy (PTT/PDT) against Methicillin-resistant Staphylococcus aureus (MRSA), but their inherent instability under pH and thermal stress limits therapeutic utility. This study evaluated polysaccharide-based stabilization systems for butterfly pea anthocyanin extract (BPFE) and assessed their photosensitizer performance through in silico and in vitro approaches. Dried flower extraction using 60% ethanol with 30-minute maceration and 45-minute ultrasonic-assisted extraction yielded a total anthocyanin content of 5.037 ± 0.395 mg CGE/L with a photothermal efficiency of 52.34 ± 7.93% at 450 nm and 22.21 ± 2.35% at 550 nm. Molecular docking against penicillin-binding protein 2a or PBP2a (PDB: 1MWU) showed that all 18 screened compounds demonstrated binding affinities of −7.4 to −11.1 kcal/mol. The extract at 8% produced an inhibition zone of 10.67 ± 0.94 mm against S. aureus (p < 0.0001), establishing the minimum inhibitory concentration. Among six polysaccharide stabilization systems evaluated, the freeze-dried konjac glucomannan system (F-KJC) demonstrated the most consistent pH stability and lowest thermodynamic degradation (23.85% vs. 39.80% for BPFE over six freeze-thaw cycles), supported by FTIR evidence of non-covalent hydrogen bonding. Singlet oxygen quantum yield of F-KJC (Φ = 0.4740) exceeded BPFE (Φ = 0.3014). Under 550 nm irradiation, F-KJC significantly inhibited MRSA growth compared with non-irradiated controls, while 450 nm irradiation did not produce a statistically significant photothermal enhancement. These findings support polysaccharide stabilization, particularly the freeze-dried konjac system, as a viable strategy for enhancing the photosensitizer performance of butterfly pea anthocyanins against MRSA.